Investigation of Pressure Effect on Structure of 3Al2O3.2SiO2 System - Pham, Tri Dung (H. : ĐHQGHN, 2020)
The paper presents research results of structure of the Mullite system (3Al2O3.2SiO2) by Molecular Dynamics simulation (MDs) using the Born–Mayer– Huggins pair interaction and periodic boundary conditions. The simulation is performed with model of 5250 atoms at different pressure and at 3500 K temperature. The structural properties of the system have been clarified through analysis of the pair radial distribution function, the distribution of coordination number, the bond angle and the link between adjacent TOx units.